Effects of γ‐Aminobutyric acid transporter 1 inhibition by tiagabine on brain glutamate and γ‐Aminobutyric acid metabolism in the anesthetized rat In vivo. Issue 7 (6th February 2015) - Patel, Anant B.; de Graaf, Robin A.; Rothman, Douglas L.; Behar, Kevin L.
Abstract : γ‐Aminobutyric acid (GABA) clearance from the extracellular space after release from neurons involves reuptake into terminals and astrocytes through GABA transporters (GATs). The relative flows through these two pathways for GABA released from neurons remains unclear. This study determines the effect of tiagabine, a selective inhibitor of neuronal GAT‐1, on the rates of glutamate (Glu) and GABA metabolism and GABA resynthesis via the GABA–glutamine (Gln) cycle. Halothane‐anesthetized rats were administered tiagabine (30 mg/kg, i.p.) and 45 min later received an intravenous infusion of either [1, 6‐ 13 C2 ]glucose ( in vivo ) or [2‐ 13 C]acetate (ex vivo). Nontreated rats served as controls. Metabolites and 13 C enrichments were measured with 1 H‐[ 13 C]‐nuclear magnetic resonance spectroscopy and referenced to their corresponding endpoint values measured in extracts from in situ frozen brain. Metabolic flux estimates of GABAergic and glutamatergic neurons were determined by fitting a metabolic model to the 13 C turnover data measured in vivo during [1, 6‐ 13 C2 ]glucose infusion. Tiagabine‐treated rats were indistinguishable ( P  > 0.05) from controls in tissue amino acid levels and in 13 C enrichments from [2‐ 13 C]acetate. Tiagabine reduced average rates of glucose oxidation and neurotransmitter cycling in both glutamatergic neurons (↓18%, CMRglc(ox)Glu : control, 0.27 ± 0.05 vs. tiagabine, 0.22 ± 0.04 µmol/g/min; ↓11%, Vcyc(Glu–Gln) : control 0.23 ± 0.05 vs. tiagabine 0.21 ± 0.04 µmol/g/min) and GABAergic neurons (↓18–25%, CMRglc(ox)GABA : control 0.09 ± 0.02 vs. tiagabine 0.07 ± 0.03 µmol/g/min; Vcyc(GABA–Gln) : control 0.08 ± 0.02 vs. tiagabine 0.07 ± 0.03 µmol/g/min), but the changes in glutamatergic and GABAergic fluxes were not significant ( P  > 0.10). The results suggest that any reduction in GABA metabolism by tiagabine might be an indirect response to reduced glutamatergic drive rather than direct compensatory effects. © 2015 Wiley Periodicals, Inc.